In Silico Assessment of GSK-3? Inhibition Activity by Secondary Metabolites of Centella asiatica in the Development of Alzheimer’s Therapy - Azariani, Wiwin; Ananto, Agus Dwi; Maulidya, Selvira Anandia Intan (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2025)
Alzheimer’s disease involves excessive activity of glycogen synthase kinase-3? (GSK-3?), leading to tau hyperphosphorylation and neurofibrillary tangle formation. This study evaluated the potential of secondary metabolites from Centella asiatica as GSK-3? inhibitors using in silico molecular docking. The GSK-3? structure (PDB ID: 1Q5K) and ten test compounds were docked using YASARA-structure, with method validation yielding an RMSD of 1.890 Å. Naringin, luteolin, and betulinic acid demonstrated the strongest binding affinities -9.2670, -8.1520, and -7.9730 kcal/mol, surpassing the native ligand. Naringin and luteolin interacted with key ATP-binding residues (Asp133, Tyr134, Val135, Lys85), indicating strong competitive inhibitory potential. These findings suggest that C. asiatica metabolites, particularly naringin and luteolin, are promising natural candidates for GSK-3? inhibitor Alzheimer’s therapy. Keywords: Centella asiatica; GSK-3?; Molecular Docking; Alzheimer’s Disease; Secondary Metabolites